Global Financial Crisis, Protectionism and Current Account Deficit: South Africa on the Brink? - Andreas Freytag; Sebastian Voll; Peter Draper (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2009)
The current financial and economic crisis has again raised fears in emerging market economies of capital flight or a sudden stop of capital inflows. Especially the latter is intensively discussed in South Africa. We try to evaluate the danger by focusing on the sustainability of current account deficit in this country during the last years and the long term economic policy developments. We argue that the macroeconomic as well as the relevant microeconomic policy variables speak against a sudden stop. To lower this risk further, the microeconomic environment has to be improved considerably in the next years. This includes mainly reforms in the areas of infrastructure, competition and trade policy.
urn:nbn:de:gbv:27-20100727-132942-0
Keywords: F32; F41; H54; 330